Project Overview of the Beijing–Arizona Sky Survey. (14th April 2017) - Zou, Hu; Zhou, Xu; Fan, Xiaohui; Zhang, Tianmeng; Zhou, Zhimin; Nie, Jundan; Peng, Xiyan; McGreer, Ian; Jiang, Linhua; Dey, Arjun; Fan, Dongwei; He, Boliang; et al.
Abstract: The Beijing–Arizona Sky Survey (BASS) is a wide-field two-band photometric survey of the northern Galactic Cap using the 90Prime imager on the 2.3 m Bok telescope at Kitt Peak. It is a four-year collaboration between the National Astronomical Observatory of China and Steward Observatory, the University of Arizona, serving as one of the three imaging surveys to provide photometric input catalogs for target selection of the Dark Energy Spectroscopic Instrument (DESI) project. BASS will take up to 240 dark/gray nights to cover an area of about 5400 deg 2 in the g and r bands. The 5 σ limiting AB magnitudes for point sources in the two bands, corrected for the Galactic extinction, are 24.0 and 23.4 mag, respectively. BASS, together with other DESI imaging surveys, will provide unique science opportunities that cover a wide range of topics in both Galactic and extragalactic astronomy.